2010
DOI: 10.1667/rr2255.1
|View full text |Cite
|
Sign up to set email alerts
|

Prenatal Exposure to Non-ionizing Radiation: Effects of WiFi Signals on Pregnancy Outcome, Peripheral B-Cell Compartment and Antibody Production

Abstract: During embryogenesis, the development of tissues, organs and systems, including the immune system, is particularly susceptible to the effects of noxious agents. We examined the effects of prenatal (in utero) exposure to WiFi signals on pregnancy outcome and the immune B-cell compartment, including antibody production. Sixteen mated (plug-positive) female mice were assigned to each of the following groups: cage control, sham-exposed and microwave-exposed (WiFi signals at 2.45 GHz, whole body, SAR 4 W/kg, 2 h/da… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

3
18
1

Year Published

2012
2012
2017
2017

Publication Types

Select...
6

Relationship

2
4

Authors

Journals

citations
Cited by 34 publications
(22 citation statements)
references
References 28 publications
3
18
1
Order By: Relevance
“…In conclusion, our results showed no effect of in vivo exposure to GSM‐modulated RF fields on the ability of BM precursor cells to colonize lymphoid organs and differentiate in phenotypically and functionally mature T‐ and B‐lymphocytes. The present findings, together with previous studies [Gatta et al, ; Nasta et al, ; Prisco et al, ; Sambucci et al, 2010, 2011; Laudisi et al, ], do not support the hypothesis that RF radiation affects immune functions and indicate that a deleterious effect on the immune‐hematopoietic system is unlikely.…”
Section: Discussioncontrasting
confidence: 96%
See 1 more Smart Citation
“…In conclusion, our results showed no effect of in vivo exposure to GSM‐modulated RF fields on the ability of BM precursor cells to colonize lymphoid organs and differentiate in phenotypically and functionally mature T‐ and B‐lymphocytes. The present findings, together with previous studies [Gatta et al, ; Nasta et al, ; Prisco et al, ; Sambucci et al, 2010, 2011; Laudisi et al, ], do not support the hypothesis that RF radiation affects immune functions and indicate that a deleterious effect on the immune‐hematopoietic system is unlikely.…”
Section: Discussioncontrasting
confidence: 96%
“…Over the years, several studies investigated the effects of RF in a wide variety of biological models, but conclusions were often contradictory. Our previous work investigated the effects of RF on the immune system in adult and developing animals [Gatta et al, ; Nasta et al, ; Sambucci et al, 2010, 2011; Laudisi et al, ]. In adult animals, cells of the immune‐hematopoietic system (leukocytes, erythrocytes, and megakaryocytes) are derived from hematopoietic stem cells residing in the BM [Nagasawa, ].…”
Section: Discussionmentioning
confidence: 99%
“…During exposure (or sham exposure) mice were restrained in transparent cylindrical polymethyl‐methacrylate jigs to obtain the defined SAR level, as already described [Sambucci et al, 2010]. Mice were placed with their posterior part on the side of the field origin and maintained with the caudal axis parallel to the direction of the field propagation.…”
Section: Methodsmentioning
confidence: 99%
“…In a recent study, we found that prenatal exposure to WiFi signals does not affect pregnancy outcome and B cell development [Sambucci et al, 2010]. We extended our research to the effects of prenatal exposure to MW‐EMF on the T lymphocyte population, considering the pivotal role played by T cells in the immune response, the requirement of a specific organ (thymus) for their differentiation, and the changes occurring in these cells due to dramatic age/gender‐related differences.…”
Section: Introductionmentioning
confidence: 99%
“…On other hand, Sambucci et al [14] found that prenatal exposure to Wi-Fi signals during gestation did not exhibited any bad effect on pregnancy outcome. A study in 2013 by Poulletier de Gannes et al [15], did not indicate any potential effects due to in-utero WiFi signals exposure at average 1 h/day even at high SAR levels 4 W/kg.…”
Section: Introductionmentioning
confidence: 97%